COVID-19 Vaccine Uptake and Influence of Mass Media: A Cross-Sectional Survey on Community People of Bangladesh - Jui, Smarnima Ghosh; Dey, Pronoy Vushon; Shill, Lincon Chandra; Tonni, Fariya Monir; Hussen, Shakhawat (International Multidisciplinary Research Journal, 2022)
This work aimed to appraise the mass media influence on getting Bangladeshi people vaccinated during the second wave of the coronavirus disease 2019 (COVID-19) pandemic. A cross-sectional study was performed among 1012 eligible respondents using a self-administered questionnaire to obtain data collected in March and April 2021 that assessed 1) the participant demographics, 2) perception towards beliefs and attitudes of COVID-19 vaccination via 5 items, 3) perception towards COVID-19 vaccination barriers via 5 items, 4) exposure to different media for COVID-19 vaccine news via 5 items, and 5) media's credibility in providing key information on COVID-19 vaccines via 5 items. Data were analyzed with frequency, mean and standard deviation of responses on each statement. Multivariable logistic regression analysis was carried out. About 1012 participants were analysed (mean age ± standard error = 45.9 ± 10.6 years, range above 18 years). Most of the participants had positive responses with a high mean score for the media's credibility in providing key information on COVID-19 vaccines (4.46 ± 0.57), perception towards COVID-19 vaccination beliefs and attitudes (3.82 ± 0.78) and exposure to different media for COVID-19 vaccine news (3.76 ± 0.68). Participants’ exposure to different media and media's credibility was significantly associated with high adoption of getting vaccinated (AOR = 1.3, 95% CI: 1.1–1.3, p<0.05; AOR = 3.1, 95% CI: 1.8–5.7, p<0.001, respectively). Research has shown that credible information about vaccines found in the media raised a person's level of motivation by raising awareness and contributed significantly to vaccine adoption.